Features of income taxes accounting (Journal of Economic Research & Business Administration, 2016)
Currently one of the most important challenges facing the domestic companies is the correct disclosure of their operating profits. Tax conse quences of transactions reflected in the financial statements are taken into account in determining current tax liabilities. The theoretical basis of the study has relied on the provisions of IAS 12 “Income Taxes”, the scientific works of domestic and foreign authors on accounting and taxation. The methodological basis of research are the principles of scientific methodol ogy, including an integrated system approach, methods of analysis and synthesis.The causes of deferred taxes are determined and examined. A con ceptual framework for use in the practice of Kazakhstan’s accounting for deferred taxes is proposed based on a detailed study of the definitions and scope of IAS 12.